2015
DOI: 10.12738/estp.2015.4.2322
|View full text |Cite
|
Sign up to set email alerts
|

The Mathematics Education I and II Courses’ Effect on Teacher Candidates’ Development of Number Sense

Abstract: The purpose of this research is to examine the number sense performance of the classroom teacher candidates taking the Mathematics Education I and II courses. Moreover, it investigates whether there is a change in the number sense performance of the teacher candidates following the Mathematics Education I and II courses. Embedded experimental design was used a mixed methods research design. Pretest-posttest weak experimental design was used in the quantitative part of the study, and a case study for the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Given the studies concluding that improvement of number sense skills increases mathematics achievements in years to come (Jordan et al, 2007; Mazzocco & Thompson, 2005; McGuire et al, 2012), lack of instruments that aim to identify number sense skills of primary school students raises concerns. Studies on number sense have been performed with pre‐school students (Aunio et al, 2004, 2006; Howell & Kemp, 2010; Jordan et al, 2007, 2010), primary school students from Grade 1 to Grade 4 (Çekirdekci et al, 2016; Mohamed & Johnny, 2010; Olkun et al, 2015; Yang & Li, 2008; Zanzali & Ghazali, 2002), and elementary school students from Grade 5 to Grade 8 (Akkaya, 2016; Harç, 2010; İymen & Duatepe Paksu, 2015; Kayhan Altay, 2010; Kayhan Altay & Umay, 2013; Lin et al, 2016; Şengül & Gülbağcı Dede, 2013; Torbeyns & Verschaffel, 2016; Yang et al, 2008; Yapıcı, 2013), and preservice teachers (Gülbağcı Dede, 2015; Şengül, 2013; Şenol et al, 2015; Yaman,2015a, 2015b). Among these studies, there are limited number of research works about measuring number sense skills and test development, especially in primary schools.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the studies concluding that improvement of number sense skills increases mathematics achievements in years to come (Jordan et al, 2007; Mazzocco & Thompson, 2005; McGuire et al, 2012), lack of instruments that aim to identify number sense skills of primary school students raises concerns. Studies on number sense have been performed with pre‐school students (Aunio et al, 2004, 2006; Howell & Kemp, 2010; Jordan et al, 2007, 2010), primary school students from Grade 1 to Grade 4 (Çekirdekci et al, 2016; Mohamed & Johnny, 2010; Olkun et al, 2015; Yang & Li, 2008; Zanzali & Ghazali, 2002), and elementary school students from Grade 5 to Grade 8 (Akkaya, 2016; Harç, 2010; İymen & Duatepe Paksu, 2015; Kayhan Altay, 2010; Kayhan Altay & Umay, 2013; Lin et al, 2016; Şengül & Gülbağcı Dede, 2013; Torbeyns & Verschaffel, 2016; Yang et al, 2008; Yapıcı, 2013), and preservice teachers (Gülbağcı Dede, 2015; Şengül, 2013; Şenol et al, 2015; Yaman,2015a, 2015b). Among these studies, there are limited number of research works about measuring number sense skills and test development, especially in primary schools.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies on number sense have been performed with pre-school students (Aunio et al, 2004(Aunio et al, , 2006Howell & Kemp, 2010;Jordan et al, 2007Jordan et al, , 2010, primary school students from Grade 1 to Grade 4 (Çekirdekci et al, 2016;Mohamed & Johnny, 2010;Olkun et al, 2015;Zanzali & Ghazali, 2002), and elementary school students from Grade 5 to Grade 8 (Akkaya, 2016;Harç, 2010;İymen & Duatepe Paksu, 2015;Kayhan Altay, 2010;Kayhan Altay & Umay, 2013;Lin et al, 2016;Şengül & Gülbağcı Dede, 2013;Torbeyns & Verschaffel, 2016;Yapıcı, 2013), and preservice teachers (Gülbağcı Dede, 2015;Şengül, 2013;Şenol et al, 2015;Yaman,2015aYaman, , 2015b. Among these studies, there are limited number of research works about measuring number sense skills and test development, especially in primary schools.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It may be stated that the number of studies on number sense in Turkey has recently increased (Çekirdekçi, Şengül, & Doğan, 2016;Gülbağcı Dede & Şengül, 2016;İymen & Duatepe Paksu, 2015;Yaman, 2015). Considering the studies on the field of number sense, while studies focusing on investigating the number sense of students, teachers and prospective teachers are frequently seen, studies investigating number sense skills especially in a certain subject in mathematics are less frequent.…”
Section: Number Sense In Terms Of Percentmentioning
confidence: 99%
“…Even so, if having a number sense ability, then students (especially preservice mathematics teachers) can solve the mathematical problems related to it better. Many studies have shown that various pre-service teacher backgrounds have low results in understanding numbers when given tests related to the component of number sense (Akkaya, 2015;Sengul, 2013;Yang, Reys, & Reys, 2009;Yaman, 2015;Aktas & Ozdemir, 2017). Besides, the results of research conducted by Sengul (2013) show that pre-service elementary teachers' number sense is still deficient and tends to use a "rule-based method" rather than "number sense" on each component tested (Koleza & Koleli, 2014).…”
mentioning
confidence: 99%